PENGARUH RASIO KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PT. ASTRA GRAPHIA Tbk. - Fakriatun Baiti; Muhammad Rimawan (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2021)
This study raises issues related to DER, ROE, CR and PER where these 4 variables have a large influence on firm value (PBV), resulting in research objectives, namely to determine the effect of DER (Debt to Equity Ratio, ROE (Return on Equity, CR (Current Ratio) and PER (Price Earning Ratio), (PER) to firm value (PBV) either partially or simultaneously at PT. Astra Graphia Tbk. for the period 2005-2019. This research is an associative study with a population of 30 years and a sample of 15 years in This research uses 2 data collection techniques, namely literature study and documentation using 3 methods of analysis, namely classical assumption test, multiple linear regression analysis and hypothesis testing. The results show that partially DER (Debt to Equity Ratio), ROE (Return on Equity) and CR (Current Ratio) has no effect on firm value while PER (Price Earning Ratio) has an effect on firm value an (PBV) at PT. Astra Graphia Tbk. while simultaneously DER (Debt to Equity Ratio), ROE (Return on Equity) and CR (Current Ratio), PER (Price Earning Ratio) affect firm value (PBV). Keywords : Rasio Keuangan, Nilai Perusahaan, Laporan Keuangan